In Silico molecular docking and molecular dynamic simulation of transferrin coated Phenytoin loaded SLNs with molecular targets of epilepsy - Ahmad Zeb; Hussain Ali; Jehan Zeb Khan; Fawad Ali Shah; Abdullah Alattar; Fawaz E. Alanazi (PLoS ONE, 2025)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures, affecting millions of people worldwide. Phenytoin is a widely used antiepileptic drug, but its therapeutic efficacy is limited by poor brain penetration and undesirable side effects. We have investigated the drug against the selected candidate’s protein target using Insilco analysis to check the mode of action in real time system. This makes Phenytoin a promising therapeutic drug for the management of different targets involved in Epilepsy disease. Considering this, using a wide range of computer aided drug-designing approaches, high interactions with the protein targets have been inferred against drug molecule Phenytoin. Eight receptors against Phenytoin molecules showed binding interactions during molecular docking but the top four i.e. Bcl-2, BDNF, IL-1β and Caspase showed high binding affinities with docking score of 7.8 kcal/mol, 7.7. kcal/mol. 7.4 kcal/mol and 7.1 kcal/mol respectively. The compound Phenytoin interacts with several important active side residues in the active domain of all the receptors which was further validated via molecular dynamic simulations for 100 ns time intervals. Furthermore, the complexes of Phenytoin reveal very stable dynamics with average RMSD, RMSF and ROG values with stable carbon-alpha atoms confirmation at different intervals. In conclusion, these molecules are promising and require experimental validation to prove them as epilepsy inhibitors.